Implikasi Hukum Internasional terhadap Praktik Genosida Etnis Rohingya di Myanmar: Sebuah Kajian Normatif - P, Ipong Gawi; Dewi, Mira Nila Kusuma; Sani, Asrul; Akmal, Nur; N, Nasria; Ilahi, Rahmat; H, Herianto (Media Hukum Indonesia (MHI), 2026)
The humanitarian crisis affecting the Rohingya ethnic group in Myanmar represents one of the gravest forms of serious human rights violations that demands profound global attention. The manifestation of systematic actions—including mass killings, forced deportations, sexual violence, and policies of citizenship deprivation—strongly indicates the existence of genocidal practices as standardized under the Convention on the Prevention and Punishment of the Crime of Genocide of 1948. This study analytically examines the conformity of the actions undertaken by Myanmar’s authorities with the constitutive elements of genocide within the framework of international law, while also assessing the scheme of state responsibility for such crimes. Employing a normative legal research method with statutory and conceptual approaches, this study concludes that the series of discriminatory policies and widespread violence fulfill the criteria of both actus reus and mens rea of genocide. As a legal consequence, Myanmar bears full responsibility under international law, thereby necessitating the active involvement of the international community in the enforcement of justice and in preventive efforts to avoid the recurrence of similar crimes.